PROGRAM KAMPUNG LITERASI BAGI ANAK-ANAK USIA SD DI WILAYAH RT 03 RW 16, KELURAHAN MEKARJAYA, KECAMATAN SUKMAJAYA, DEPOK - Nur Irwansyah; Arinah Fransori; Azhari Ikhwati (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
This form of community service is the implementation of the Literacy Village Program in the RT 03 RW 16 area, Mekarjaya Village, Sukmajaya District, Depok by providing educational reading books for elementary school-age children that have educational value. The activities carried out for the children there are in the form of reading books that have educational value. There are several stages that will be carried out by the Abdimas team. The first stage, namely finding out and identifying the problems felt by partners and subjects of community service, namely elementary school-age children. You do this by asking Mitra Abdimas as the Head of the RT there and making observations in the RT 03 area to see the activities of the children there. The second stage is to provide a place to organize the Literacy Village Program for the children there. Apart from that, the community service team provided reading books as well as prepared the necessary equipment to be used for the children's activities there. The method used in this community service is to use the literacy learning method. The literacy learning method is a Select-Know-Read-Invented-Discussion (PiKeBaDiCi) method, namely 1) choosing and recognizing books; 2) reading books; 3) discuss the theme; and 4) creating work. The existence of this community service activity can make children in the RT 03 area more enthusiastic about learning and reading with their friends. The friendship between them became even closer and the boredom and boredom that they had experienced all this time disappeared and was replaced by a feeling of pleasure during the reading activity. The feeling of pleasure from participating in community service activities has an impact on children's enthusiasm for learning and reading together as well as increasing their literacy skills. The results achieved were: 1) the availability of knowledge and information services in the non-formal education pathway in the form of books and non-books, 2) school-age children increase their knowledge, skills and develop positive attitudes, so that they have better literacy skills, 3) the availability of information services to children related to 2 of the 6 components of literacy, namely literacy and numeracy.